PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 30 TAHUN 2009 TENTANG KETENAGALISTRIKAN (STUDI KASUS PEMADAMAN LISTRIK DI KECAMATAN KETAHUN) - Widya, Elda (UIN Fatmawati Sukarno Bengkulu, 2022)
en telah sesuai pada Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen dan konsumen mendapat kompensasi berdasarkan UndangUndang Nomor 30 Tahun 2009 tentang Ketenagalistrikan. pada Pasal 29 ayat (1) huruf e yang menyatakan konsumen berhak untuk mendapat ganti rugi apabila terjadi pemadaman yang diakibatkan kesalahan dan/ atau kelalaian pengoperasian oleh pemegang izin usaha penyediaan tenaga listrik. 2) Adapun faktor-faktor yang mempengaruhi terjadinya pemadaman listrik di Kecamatan Ketahun yaitu faktor eksternal dan faktor internal . faktor eksternal itu sendiri 90% disebabkan oleh faktor cuaca dimana hujan lebat di sertai angin kencang yang menyebabkan banyak pohon tumbang sehingga menyebabkan kerusakan pada instalasi gardu listrik. Dan 10% dikarenakan faktor internal seperti kerusakan pada trafo, kabel dan alat penunjang lainnya. Terkait kasus pemadaman listrik di wilayah ketahun itu 90% disebabkan oleh faktor cuaca sehingga pihak PLN tidak memberikan ganti rugi karena itu diluar dari perkiraan mereka. Kata Kunci: Perlindungan Konsumen, Undang-Undang, Pemadaman Listrik. Abstract: The formulations of this research are: 1) What is the form of legal protection for consumers related to power outages in Ketahun District? 2) What are the factors that cause blackouts in Ketahun District? This type of research is field research (field research). Collecting data by collecting information through in-depth interviews with a number of respondents from employees of PT. PLN (Persero) Rayon Arga Makmur and employees of PT. PLN (Persero) Rayon Arga Makmur, Ketahun Guard Office in Ketahun District and some consumers use electricity in Ketahun sub-district. This study concludes that: 1) The form of legal protection of PT. PLN (Persero) to consumers has complied with Law Number 8 of 1999 concerning Consumer Protection and consumers are compensated based on Law Number 30 of 2009 concerning Electricity. in Article 29 paragraph (1) letter e which states that consumers have the right to receive compensation in the event of a blackout caused by errors and/or negligence in operation by the holder of the electricity supply business license. 2) The factors that influence the occurrence of blackouts in Ketahun District are external factors and internal factors. 90% of external factors are caused by weather factors where heavy rains are accompanied by strong winds which cause many trees to fall, causing damage to the installation of electrical substations. And 10% due to internal factors such as damage to transformers, cables and other supporting equipment. Regarding the case of blackouts in the area that year, 90% were caused by weather factors so that PLN did not provide compensation because it was beyond their estimates. Keywords: Consumer Protection, Laws, Power Outages.